A two-dimensional PtS2/BN heterostructure as an S-scheme photocatalyst with enhanced activity for overall water splitting. Issue 43 (1st November 2022) - Wang, Biao; Yuan, Hongkuan; Yang, Tie; Wang, Peng; Xu, Xiaohui; Chang, Junli; Kuang, Minquan; Chen, Hong
Abstract : The optical absorption spectra of the PtS2 /BN heterojunction. Abstract : Photocatalytic hydrogen production from water is a sustainable solution to the environmental pollution and energy crises. Encouraged by the successful synthesis of PtS2 and BN nanosheets and their suitable band edges, we have designed a PtS2 /BN bilayer heterojunction and investigated its electronic and optical properties for the first time based on hybrid DFT calculations. In this system, the built-in electric field and band edge bending can retain useful electrons on the conduction band of BN and holes on the valence band of PtS2, which endow this system with a stronger redox ability. Meanwhile, this electric field can efficiently separate photoinduced electron–hole pairs and improve the photocatalytic efficiency. Compared with BN and PtS2 single layers, the PtS2 /BN heterojunction with its smaller bandgap can make better use of visible and infrared light. Additionally, we have studied the effect of applied strain on the electronic and optical properties. This work aims to provide a method for constructing high-efficiency BN-based photocatalysts and illuminating the electron migration mechanism in step-scheme (S-scheme) heterostructures. We have found that the PtS2 /BN bilayer heterojunction is a promising S-scheme photocatalyst for overall water decomposition.